A study on the general banking activities of Prime Bank Limited, Gulshan Branch - Bhuyain, Abu Sadat Md. Sayem (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.